Sunday

April 20, 2014

April 20, 2014

Posted by **Anonymous** on Saturday, April 17, 2010 at 3:10am.

- Algebra -
**drwls**, Saturday, April 17, 2010 at 7:33am(6h-1)(4h^2 +h+3)

= 4h^2(6h-1)

+ h(6h-1)

+ 3(6h-1)

= ?

Multiply them out and combine the terms with the same exponent of h, such as

-4h^2 +6h^2 = 2h^2

**Related Questions**

algebra - -(4h-1)/1+h; h=2 the 4h-1 is on top of 1+h please can someone explain

H NMR - C4 H10 O2 ppm = 3.25 singlet 6H ppm = 3.45 singlet 4H

math(did i do this right) - did i factorise this correctly?? 8h^2-4h 2h(4h-2) 8h...

Algebra - -6h + 4 - 3 + h = 11 4-3-11=6h-h -10=5h -2=h

Algebra - factor trinomial This is what I have so far dont know where to go from...

algebra - Need help for a test show all steps to solve problem evaluate the ...

calculus - f (4 + h) - f (4) = 4h^2 + 4h (a) What is f '(4)? (b) What is the ...

chemistry - use the following data to calculate the mean bond enthalpy values ...

algebra - 1/6h=9

algebra 2 - (-5g^5h^6)^2(g^4h^2)^4